2018
DOI: 10.2169/internalmedicine.0549-17
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nasopancreatic Drainage for Severe Post-endoscopic Retrograde Cholangiopancreatography Pancreatitis: A Case Series

Abstract: Five patients complaining of severe pain due to severe post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) underwent nasopancreatic drainage (NPD) placement. Pain relief was achieved on the second, fourth, and fifth day in three, one, and one patients, respectively. Four patients underwent pancreatic juice culture; all were positive. Our results suggest that NPD can relieve severe PEP with severe pain. Bacteria-induced protease-activated receptor-2 activation may be associated with PEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nevertheless, no severe PEP was observed after NPD placement. Kawaguchi et al reported that NPD placement helps prevent PEP exacerbation [ 32 ]. NPD placement, similar to a pancreatic duct stent, has a preventive effect on acute pancreatitis in patients with suspected pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no severe PEP was observed after NPD placement. Kawaguchi et al reported that NPD placement helps prevent PEP exacerbation [ 32 ]. NPD placement, similar to a pancreatic duct stent, has a preventive effect on acute pancreatitis in patients with suspected pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NPD has a lower risk of retrograde gut bacterial infection than stent placement. A previous case series demonstrated that NPD for severe PEP is effective for early pain relief and might attenuate disease progression [15]. There is currently insufficient evidence that pancreatic duct decompression via NPD during the early phase of AP improves the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…However, although hyperamylasemia is relatively common [ 36 ], the ratio of PEP is not always high, and severe PEP is rare [ 36 , 40 ]. As pancreatic juice drainage using a nasopancreatic drainage tube can be used to treat acute pancreatitis [ 46 ], the incidence of PEP during SPACE is low. Another problem with SPACE is that it impels the patient to stay in the hospital for several days because of the maintenance of the placed nasopancreatic tube, although meals are not restricted.…”
mentioning
confidence: 99%